The visual mismatch negativity elicited with visual speech stimuli - Files, Benjamin T.; Auer, Edward T.; Bernstein, Lynne E. (Frontiers in Human Neuroscience, 2013)
The visual mismatch negativity (vMMN), deriving from the brain’s response to stimulus deviance, is thought to be generated by the cortex that represents the stimulus. The vMMN response to visual speech stimuli was used in a study of the lateralization of visual speech processing. Previous research suggested that the right posterior temporal cortex has specialization for processing simple non-speech face gestures, and the left posterior temporal cortex has specialization for processing visual speech gestures. Here, visual speech consonant-vowel (CV) stimuli with controlled perceptual dissimilarities were presented in an electroencephalography (EEG) vMMN paradigm. The vMMNs were obtained using the comparison of event-related potentials (ERPs) for separate CVs in their roles as deviant versus their roles as standard. Four separate vMMN contrasts were tested, two with the perceptually far deviants (i.e., “zha” or “fa”) and two with the near deviants (i.e., “zha” or “ta”). Only far deviants evoked the vMMN response over the left posterior temporal cortex. All four deviants evoked vMMNs over the right posterior temporal cortex. The results are interpreted as evidence that the left posterior temporal cortex represents speech stimuli that are perceived as different consonants, and the right posterior temporal cortex represents face gestures that may not be discriminable as different CVs.